THE LEADING BRANCHES OF KARSHI CITY ENTERPRISES, DURING THE PERIOD OF THE BUKHARA EMIRATE - Karimov Bahrom (American Journals Publishing, 2024)
Kashkadarya oasis in the economic life of the Bukhara emirate was distinguished by its specialization in agriculture, handicrafts and animal husbandry. Each district in the Kashkadarya oasis contributed its share to various sectors of the economy based on its natural climate and geographical conditions. Areas of the oasis suitable for artificial irrigation - mainly Shahrisabz, Kitab and Karshi, and partially Yakkabag beklik’s are settlements engaged in sedentary farming and the grain, fruit and vegetable products grown in these areas were of great importance for the economy of the emirate.